2020
DOI: 10.1007/s13238-020-00784-w
|View full text |Cite
|
Sign up to set email alerts
|

Role of gut microbiota in identification of novel TCM-derived active metabolites

Abstract: Traditional Chinese Medicine (TCM) has been extensively used to ameliorate diseases in Asia for over thousands of years. However, owing to a lack of formal scientific validation, the absence of information regarding the mechanisms underlying TCMs restricts their application. After oral administration, TCM herbal ingredients frequently are not directly absorbed by the host, but rather enter the intestine to be transformed by gut microbiota. The gut microbiota is a microbial community living in animal intestines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(50 citation statements)
references
References 157 publications
(242 reference statements)
0
39
0
Order By: Relevance
“…These results indicated that the PF had the positive effect of regulating the intestinal flora and protecting intestinal tissue. In previous research, phytogenic feed additives have been shown to suppress harmful bacteria, select beneficial bacteria by controlling the intestinal microbial ecosystem, and favoring healthier microbial groups ( Guo et al., 2004 ; Tiihonen et al., 2010 ; Mao, 2016 ; Lin et al., 2021 ). Moreover, introduction of probiotics in the PF had the positive effect of reconstructing the intestinal flora of infected chicks.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that the PF had the positive effect of regulating the intestinal flora and protecting intestinal tissue. In previous research, phytogenic feed additives have been shown to suppress harmful bacteria, select beneficial bacteria by controlling the intestinal microbial ecosystem, and favoring healthier microbial groups ( Guo et al., 2004 ; Tiihonen et al., 2010 ; Mao, 2016 ; Lin et al., 2021 ). Moreover, introduction of probiotics in the PF had the positive effect of reconstructing the intestinal flora of infected chicks.…”
Section: Discussionmentioning
confidence: 99%
“…The intestinal flora affects host physiology by producing thousands of metabolites. The crosstalk between the host and microorganisms exerts an influence by altering signalling pathways and metabolic reactions ( Krautkramer et al, 2020 ; Lin et al, 2020 ). To better understand this interaction, we studied the change in metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…However, drug approval in the West usually requires a pure molecule with a precisely defined formulation to demonstrate single agent activity before combinations can be tested, and we are convinced that many TCM molecules with useful single agent activity remain to be discovered. Modulation of the gut microbiome by TCMs is an important research frontier ( Lin et al, 2019b ; Lin et al, 2021 ; Zhang et al, 2020a ; Li et al, 2021b ). Here, we will only touch on this topic in the context of immune regulators that act locally in the gut.…”
Section: Introductionmentioning
confidence: 99%
“…The blue arrow in Figure 1 indicates direct action of TCM molecules on gut microbes, which is an important research frontier that we do not discuss. For reviews see Lin et al, 2019b ; Lin et al, 2021 ; Zhang et al, 2020a ; Li et al, 2021b ; Chen et al, 2016 .…”
Section: Introductionmentioning
confidence: 99%